If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + 7a + 6 = 0 Reorder the terms: 6 + 4a + 7a = 0 Combine like terms: 4a + 7a = 11a 6 + 11a = 0 Solving 6 + 11a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 11a = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 11a = 0 + -6 11a = 0 + -6 Combine like terms: 0 + -6 = -6 11a = -6 Divide each side by '11'. a = -0.5454545455 Simplifying a = -0.5454545455
| 2y+2x+16=60 | | 5a+8+(-2a)=7 | | 8-(3*-2)-2= | | 121.824=-7.52(1+4k) | | 251/500=x | | -2*(x-3)=18 | | 50-9x=18+7x | | 91/2/2 | | 1/9(9x-4)=(x-4)/(18) | | m+n=20 | | 4(5b-3)= | | 4-6k-5k= | | -2*-9-3*-3+1= | | 11c-88=(-22)-8c | | X/2=16.5 | | 4x^2+3y=36 | | 3x+22/7+x+11/5=11 | | 54/5x=-521/5 | | 17=9+2x | | 3x^2y^-3/12x^6y^3 | | 5g+34=56 | | .28x+.18y=11.8 | | 11c-88=-22-8c | | 2x+5/6-(x-4/9)-(3x+7/2)=1/3 | | 3y=-4x^2+36 | | -(11-2x)=(x+8) | | d=n+4m | | .06x-.01y=0 | | f=34+45 | | (4x^2y^0/8x^-2)^-2*(x^-2/x^-4y^5) | | d=n | | 23-4k=3(-k+6) |